Effect of spinal monoaminergic neuronal system dysfunction on pain threshold in rats, and the analgesic effect of serotonin and norepinephrine reuptake inhibitors. (26th February 2016) - Tamano, Ryuta; Ishida, Mitsuhiro; Asaki, Toshiyuki; Hasegawa, Minoru; Shinohara, Shunji
Highlights: Intrathecal reserpine depleted the monoamines mainly in the spinal cord. The mechanical hypersensitivity was observed without depressive-like behavior. SNRIs showed analgesic effects regardless of their antidepressant actions. Abstract: Dysfunction in the central serotonin (5-HT) and norepinephrine (NE) systems cause depression and pain. Descending spinal pain modulatory pathways are important in the analgesic mechanisms of antidepressants, particularly serotonin and norepinephrine reuptake inhibitors (SNRIs). While many non-clinical studies have demonstrated the roles of central monoaminergic systems in pain, there is little evidence to illuminate the direct contribution of spinal descending pain modulatory systems independently of depressive-like behavior. To examine the effects of dysfunction of spinal monoaminergic systems on pain sensitivity, we established a rat chronic pain model by administering lumbar-intrathecal reserpine to minimize its influence on brain. Lumbar-intrathecal reserpine evoked persistent mechanical hypersensitivity and corresponding reductions in spinal 5-HT and NE concentrations (from 767.2 to 241.6 ng/g and from 455.9 to 41.7 ng/g, respectively after reserpine 30 nmol). Lumbar-intrathecal reserpine did not deplete brain monoamines or bring about depressive-like behavior in the forced swim test. Spinal monoamines depletion-induced pain sensitivity was ameliorated by lumbar-intrathecal administration of the SNRIs (duloxetine and milnacipran) in dose-dependent manners. These suggest that increased pain sensitivity could be induced by dysfunction solely of the descending pain modulatory system, regardless of depressive-like behavior, and lumbar-intrathecal administration of SNRIs could ameliorate the pain sensitivity which might be mediated by affecting the descending pain modulatory system in the spinal cord, not via their antidepressant effects.